Gut-Thyroid axis: How gut microbial dysbiosis associated with euthyroid thyroid cancer - Ishaq, Hafiz Muhammad (2022)
Thyroid cancer in humans has a fast-growing prevalence, with the most common lethal endocrine malignancy for unknown reasons. The current study was aimed to perform qualitative and quantitative investigation and characterization of the gut bacterial composition of euthyroid thyroid cancer patients. The fecal samples were collected from sixteen euthyroid thyroid cancer patients and ten from healthy subjects. The PCR-DGGE was conducted by targetting the V3 region of 16S rRNA gene, as well as real-time PCR for Bacteroides vulgatus, E.coli Bifidobacterium, Clostridium leptum and Lactobacillus were carried. High-throughput sequencing of V3+V4 region of 16S rRNA gene was performed on Hiseq 2500 platform on 20 (10 healthy & 10 diseased subjects) randomly selected fecal samples. The richness indices and comparative diversity analysis showed significant gut microbial modification in euthyroid thyroid cancer than control. At phylum level, there was significant enrichment of Firmicutes, Verrucomicrobia, while a significant decrease in Bacteroidetes was detected in the experimental group. At family statistics, significant high levels of Ruminococcaceae and Verrucomicrobiaceae, while the significant lower abundance of Bacteroidaceae, Prevotellaceae, Porphyromonadaceae, and Alcaligenaceae was after observed. It also found that the significantly raised level of Escherichia-Shigella, Akkermansia [Eubacterium]_coprostanoligenes, Dorea, Subdoligranulum, and Ruminococcus_2 genera, while significantly lowered genera of the patient group were Prevotella_9, Bacteroides and Klebsiella. The species-level gut microbial composition showed a significantly raised level of Escherichia coli in euthyroid thyroid cancer. Thus, this study reveals that euthyroid thyroid cancer patients have significant gut microbial dysbiosis. Moreover, Statistics (P<0.05) of each gut microbial taxa were significantly changed in euthyroid thyroid cancer patients. Therefore, the current study may propose new approaches to understanding thyroid cancer patients' disease pathways, mechanisms, and treatment.